Which Predisposing Factors Influence The Farmers in Compliance of Personal Protective Equipment (PPE)? - Rizky Maharja; Ade Wira Lisrianti Latief; Helmy Gani; M. Anas; Muhammad Akbar Salcha; Sri Novianti Bahar; Ria Rezeki Sudarmin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Farmers who work in the agricultural sector are workers who need attention in the field of occupationalsafety and health because of the combinations of hazard and risk. One of them is the risk of pesticides, suchas poisoning to death. To prevent it, the use of appropriate PPE is the best solution, but most farmers do notcomply with them. The specific purpose of this study was to find in-depth information about the use of PPEby vegetable farmers. It is a qualitative study with a phenomenological approach to study the phenomenonof PPE non-compliance among vegetable farmers. Sampling was carried out by using purposive samplingtechnique, which involved 18 farmers from different village. Data were analyzed using content analysis.The result showed that the farmers had worked for more than 10 years. They knew the function of PPEand the impact of not using it, education had no impact on compliance of using PPE based on the majorityof farmer’s education. Also, the farmers can not provide the nominal for purchasing PPE, because it isincidental so income has not contributed to compliance of using PPE. And although most of the farmershave a good attitude to compliance of using PPE, it has no impact on compliance of using PPE in vegetablefarmers. It can conclude that the predisposing factors in this study are considered insufficient to make apositive contribution to compliance with the use of PPE.